Spontaneous uterine cornual rupture at 26 weeks' gestation in an interstitial heterotopic pregnancy following in vitro fertilization. Issue 5 (16th December 2015) - Paradise, Courtney; Carlan, S.J.; Holloman, Conisha
ABSTRACT: Interstitial implantation in a heterotopic pregnancy is extremely rare, and despite currently available diagnostic modalities, early identification of an interstitial ectopic pregnancy remains difficult. This report describes a case of spontaneous cornual rupture at 26 weeks' gestation in a woman with diamniotic dichorionic twins that resulted in live births. The patient had previously undergone laparoscopic bilateral salpingectomy, and the pregnancy was conceived with in vitro fertilization. Interstitial implantation in a heterotopic pregnancy can go unrecognized, resulting in increased maternal and infant morbidity and mortality. © 2015 Wiley Periodicals, Inc. J Clin Ultrasound 44 :322–325, 2016